Silicon Nitride-on-Insulator Photonics Polarisation Convertor - D. M. Mokhovikov; E. S. Barbin; T. G. Nesterenko; A. A. Talovskaya; A. S. Myrzakhmetov; I. V. Kulinich; P. F. Baranov; D. P. Il’yaschenko (Приборы и методы измерений, 2024)
Photonic integrated circuits constitute a vital component of contemporary telecommunications systems, facilitating traffic management and reducing energy consumption. However, the integration of these components presents a significant challenge in the form of high polarization sensitivity, which has the potential to limit the overall performance of the device. The objective of this study was to develop a design method and fabrication technology for polarization converters based on silicon nitride-on-insulator. The design of the polarization converters was optimised through the utilisation of finite element method simulations, conducted using the ANSYS Lumerical software. The device features an asymmetric rib waveguide, which facilitates efficient polarisation rotation. The technological implementation comprised plasma chemical vapor deposition of silicon nitride films, three-dimensional laser lithography, and reactive ion etching. A technological assessment determined that the reproducibility tolerance was ± 60 nm. To address this limitation, a mirrored section was incorporated into the polarization converter design, thereby increasing the allowable fabrication tolerance to ± 215 nm without compromising device performance. The optimised polarization converter exhibited a high level of polarization rotation efficiency, reaching 96.3 %, and an output power of 98.32 %. The utilisation of an asymmetric rib waveguide was pivotal in attaining these outcomes, facilitating the transfer of optical power from fundamental transverse electric to fundamental transverse magnetic modes. The incorporation of a mirrored section enhanced the device's manufacturability, maintaining performance despite geometric deviations. These findings highlight the robustness of the proposed design under typical fabrication constraints. This study presents a novel design and fabrication method for silicon nitride on insulator-based polarization converters. The proposed approach improves efficiency and stability. These results provide a foundation for future advancements in integrated photonics, with potential applications in telecommunications and beyond.